Frontostriatal functional connectivity underlies self-enhancement during social evaluation. Issue 8 (4th January 2022) - Parrish, Michael H; Dutcher, Janine M; Muscatell, Keely A; Inagaki, Tristen K; Moieni, Mona; Irwin, Michael R; Eisenberger, Naomi I
Abstract: Self-enhancement, the tendency to view oneself positively, is a pervasive social motive widely investigated in the psychological sciences. Relatively little is known about the neurocognitive mechanisms underlying this motive, specifically in social-evaluative situations. To investigate whether positive emotion regulation circuitry, circuitry involved in modulating positive affect, relates to the self-enhancement motive in social contexts, we conducted an functional magnetic resonance imaging (fMRI) study in a healthy young adult sample. We hypothesized that self-enhancement indices (state and trait self-esteem) would relate to greater functional connectivity between right ventrolateral prefrontal cortex (RVLPFC), a region implicated in emotion regulation, and the ventral striatum (VS), a region associated with reward-related affect, during a social feedback task. Following social evaluation, participants experienced stable or decreased state self-esteem. Results showed that stable state self-esteem from pre- to post-scan and higher trait self-esteem related to greater RVLPFC–VS connectivity during positive evaluation. Stable-state self-esteem also related to greater RVLPFC–VS connectivity during negative evaluation. Moreover, RVLPFC activation during all types of feedback processing and left VS activation during negative feedback processing was greater for participants with stable-state self-esteem. These findings implicate neurocognitive mechanisms underlying emotion regulation in the self-enhancement motive and highlight a pathway through which self-enhancement may restore feelings of self-worth during threatening situations.